Inference on sets in finance - Victor Chernozhukov; Emre Kocatulum; Konrad Menzel (Centre for Microdata Methods and Practice (cemmap), 2012)
In this paper we introduce various set inference problems as they appear in finance and propose practical and powerful inferential tools. Our tools will be applicable to any problem where the set of interest solves a system of smooth estimable inequalities, though we will particularly focus on the following two problems: the admissible meanvariance sets of stochastic discount factors and the admissible mean-variance sets of asset portfolios. We propose to make inference on such sets using weighted likelihoodratio and Wald type statistics, building upon and substantially enriching the available methods for inference on sets.
Keywords: C10; C50; 330; Hansen-Jagannathan set; Marokowitz set; Inference